The influence of hand depiction types on behavioural patterns in laterality judgments - Aneet K. Saran; Stephen Wood; Jonathan J. Marotta (PLoS ONE, 2026)
According to Motor Simulation Theory, cognitive states such as kinesthetic motor imagery activate the motor system in a manner similar to overt motor execution. Action simulation can be implicitly triggered when individuals unconsciously simulate an action, as in the Hand Laterality Judgment Task (HLJT). Studies employing the HLJT use different hand depictions, which may influence behavioural performance. The aim of the present study was to examine whether hand depiction type (realistic hands versus line drawings) influences performance on the HLJT. Sixty-two younger adults completed the HLJT using both realistic and line-drawing representations of hands. Results demonstrated significant effects of orientation, with faster and more accurate responses observed at less challenging orientations and a medial-over-lateral advantage (MOLA) evident for palm-view stimuli. Overall, performance declined as hand orientation became increasingly biomechanically demanding. Importantly, the effects of hand depiction type varied as a function of viewpoint and orientation. For back-view stimuli, line drawings elicited faster responses than realistic hands at 0° and 90° lateral orientations. In contrast, for palm-view stimuli, line drawings elicited faster responses and higher accuracy than realistic stimuli. These findings suggest that the effects of hand depiction are not uniform across task conditions. As such, the type of hand stimulus used should be carefully considered when designing, interpreting, and comparing HLJT studies, particularly when the task is used to assess motor imagery processes.